Will Problems Arise When Banks are Exempted from Thin Capitalization Regulation? - Saragih, Arfah Habib (Jurnal Ekonomi Modernisasi, 2018)
This research was intended to provide empirical evidences that the exemption of banks from Minister of Finance Decree Number 169/PMK.010/2015 did not raise any significant problem on banks tax avoidance which was measured by effective tax rates. Quantitative method was used in this study by conducting regression-fixed effects method on unbalanced panel data. This study found that thin capitalization in banks did not impact effective tax rates significantly. Present research also found that the banks size and profitability were other determinants of the level of tax avoidance in the banks sample. Bank size and profitability had a significant and negative effect on effective tax rate.